„Eat, drink and be merry” (Luke 12:19). Food and wine in Byzantium. In honour of Professor A.A.M. Bryer, ed. L. Brubaker – K. Linardou, Aldershot – Hampshire 2007, Ashgate Publishing Limited, ss. 272. - Kokoszko, Maciej; Gibel, Katarzyna (Vox Patrum, 2009)
nie dotyczy